Agriculture, food and land: Struggles for UK post-Brexit agri-food justice. Issue 131 (May 2022) - Coulson, Helen; Milbourne, Paul
Highlights: Examines the possibilities and challenges of nurturing UK agri-food justice. Land justice is crucial to engender food system transformation. 'Public goods' approach to agri-food policy acts as a depoliticising consensus frame. The land-food nexus must be placed more prominently on the research agenda. Argues for participative, inclusive agri-food praxis based on socioecological justice. Abstract: This paper examines the possibilities and challenges of nurturing agri-food justice by using land as a foundational node in the context of the UK leaving the European Union – what has been termed 'Brexit'. Drawing upon the interconnected literatures of land justice and food justice, which have received sparse coverage in the UK, we develop an agri-food (in)justice lens to reveal the diverse contestations and struggles to transform the physical and political agri-food Brexit landscape in more socioecological just ways. Our research highlights the tensions and difficulties in addressing the complex social and environmental injustices bound up with UK agri-food relations, given the unequal power dynamics that permeate food and farming politics and policy. In particular, the research reveals the continued 'hidden' politics of historically-embedded land (in)justice. We therefore argue for greater focus on the multiscalar relationships between land and the intersecting contestations of agri-food labour, capital and knowledge. We end the paper by discussing the limitations of the nascent 'public goods' approach to agricultural policy under a purported 'Green Brexit' and arguing for participative and inclusive agri-food praxis based on land and food justice to cultivate more socioecologically just futures.